Cannabinoids and Multiple Sclerosis: A Critical Analysis of Therapeutic Potentials and Safety Concerns - Roua A. Nouh; Ahmed Kamal; Anwar Abdelnaser (MDPI AG, 2023)
Multiple sclerosis (MS) is a complicated condition in which the immune system attacks myelinated axons in the central nervous system (CNS), destroying both myelin and axons to varying degrees. Several environmental, genetic, and epigenetic factors influence the risk of developing the disease and how well it responds to treatment. Cannabinoids have recently sparked renewed interest in their therapeutic applications, with growing evidence for their role in symptom control in MS. Cannabinoids exert their roles through the endogenous cannabinoid (ECB) system, with some reports shedding light on the molecular biology of this system and lending credence to some anecdotal medical claims. The double nature of cannabinoids, which cause both positive and negative effects, comes from their actions on the same receptor. Several mechanisms have been adopted to evade this effect. However, there are still numerous limitations to using cannabinoids to treat MS patients. In this review, we will explore and discuss the molecular effect of cannabinoids on the ECB system, the various factors that affect the response to cannabinoids in the body, including the role of gene polymorphism and its relation to dosage, assessing the positive over the adverse effects of cannabinoids in MS, and finally, exploring the possible functional mechanism of cannabinoids in MS and the current and future progress of cannabinoid therapeutics.